Attitudes of palliative care clinical staff toward prolonged grief disorder diagnosis and grief interventions. Issue 4 (3rd July 2017) - Davis, Esther L.; Deane, Frank P.; Barclay, Gregory D.; Bourne, Joan; Connolly, Vivienne
ABSTRACT: Objective: The provision of psychological support to caregivers is an important part of the role of the clinical staff working in palliative care. Staff knowledge and attitudes may determine their openness to referring caregivers to a psychological intervention. We recently developed a self-help intervention for grief and psychological distress among caregivers and were interested in exploring the extent to which staff knowledge and attitudes might affect future implementation. The aims of our study were to: (1) examine the acceptability of self-help psychological intervention for caregivers among palliative care clinical staff; (2) examine potential attitudinal barriers toward prolonged grief disorder (PGD) as a diagnosis and interventions for grief; and (3) bolster staff confidence in skills and knowledge in identifying and managing caregiver psychological distress. Method: An anonymous survey was distributed among clinical staff at two inpatient units and two community health services that assessed the acceptability of self-help interventions for caregivers, attitudes about PGD diagnosis and grief intervention, and staff confidence in skills and knowledge in assessing caregiver psychological distress. Results: Overall, clinical staff were positively oriented toward self-help for caregivers and intervention for grief. They were also basically confident in their skills and knowledge. While it was positive PGD attitudes that were associated with acceptability of self-help for caregivers, it was both positive and negative PGD attitudes that were associated more specifically with a willingness to refer caregivers to such an intervention. Significance of results: Our findings are useful in highlighting the issues to be considered in the implementation of a self-help intervention within the healthcare service. Clinical staff seemed positively oriented toward engaging with a psychological intervention for caregivers and likely to act as key allies in implementation.